1985
DOI: 10.1007/bf00008941
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton communities response to a mine effluent rich in copper

Abstract: The effects of a mine effluent containing high copper levels on the structure of the .phytoplankton communities in a chain of low alkalinity and hardness oligotrophic reservoirs situated north of Portugal were studied monthly, during 1981-1982. In the reservoirs under mine influence, a shift in the dominant species have occurred. In contrast with the uncontaminated areas, more than 50% of the algal species developed lower populations. At the most polluted zone, phytoplankton density, biomass and species number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The present study found this cyanobacterium to be sensitive to As but tolerant to Cr as well as Al. The tolerance of Scenedesmus quadricauda to all the test metals in the present case is in agreement with the report on its greater copper tolerance (Oliveira, 1985). However, the other species Scendesmus bijugatus showed sensitivity to test metals.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found this cyanobacterium to be sensitive to As but tolerant to Cr as well as Al. The tolerance of Scenedesmus quadricauda to all the test metals in the present case is in agreement with the report on its greater copper tolerance (Oliveira, 1985). However, the other species Scendesmus bijugatus showed sensitivity to test metals.…”
Section: Discussionsupporting
confidence: 93%
“…The first references to the presence of the genera Synura and Mallomonas in Portuguese waters date from the late 1950s and early 1960s, respectively (Nauwerck 1959(Nauwerck , 1962. In these and later works (e.g., Rino 1969;Moita 1976;Oliveira 1985;Coutinho 1990) several species are cited, but their identifications were based exclusively on observations with the light microscope, which renders most of them doubtful. In a recent survey of 17 sites in central Portugal Santos & Leedale (1993) found 11 species of Mallomonas and 5 of Synura using TEM.…”
Section: Introductionmentioning
confidence: 99%
“…For the spanish reservoirs he found (1976) most of the AN values ranging from 0 .5 to 5 . A shift in the dominant phytoplankton species from the upper reservoir (Crucigenia tetrapedia, Quadrigula closterioide, Tabellaria flocculosa and Melosira distans) to the mine and down mine reservoir (Cosmarium tinctum), as well as a strong reduction in density and species number was observed (Oliveira, 1985) .…”
Section: Comparisons Of Primary Productivity (Pp) Chlorophyll a (Chlmentioning
confidence: 99%
“…The downstream reservoirs, Venda Nova and Salamonde are subjected to copper contamination from wastes of a copper pyrite and tungsten mine. Some studies, on copper distribution (Vale, 1982), phytoplankton (Oliveira, 1985) and zooplankton (Monteiro, 1982) were undertaken .…”
Section: Introductionmentioning
confidence: 99%